Association between sarcopenic obesity, muscle strength and risk of cardiovascular and cardiometabolic diseases in the elderly: A systematic review - Sinésio SILVA NETO, Luiz; MEDEIROS, Alessandra; TRAVASSOS, Andreia; Barbosa OSÓRIO, Neila; Ferreira NUNES, Genildo (Revista de Nutrição, 2023)
To describe the fi ndings in the literature about the association between sarcopenic obesity, muscle strength and risk factors and/or cardiometabolic or cardiovascular diseases in the elderly. A research was carried out in the following databases: Medical Literature Analysis and Retrievel System Online, Web of Science, Literatura Latino-Americana e do Caribe em Ciências da Saúde (Latin America and Caribbean Health Sciences Literature) and Capes Journals, using the following search terms in English, Spanish and Portuguese: “obesity sarcopenic” OR “sarcopenic obesity” in the title AND “cardiometabolic disease” OR “cardiovascular disease” OR “metabolic syndrome” OR “insulin resistance” in the title/abstract AND “aged” in all fields of search with the variation of the “muscle strength” descriptor in all fields of this research. Articles were selected according to the following exclusion criteria: studies evaluating only sarcopenia and the risk of cardiometabolic/cardiovascular disease in the elderly, studies evaluating only obesity and the risk of cardiometabolic/cardioascular disease in the elderly, studies that did not present the used method, studies in animals and studies that were not in Portuguese, English or Spanish. The researchers of the present study found a heterogeneity of methods for the identification of sarcopenic obesity, and a transversal cohort was used in most of the studies. It was possible to verify the association of sarcopenic obesity with risk factors and/or cardiometabolic or cardiovascular disease. Sarcopenic obesity is associated with risk factors and/or cardiometabolic or cardiovascular disease in the elderly. Establishing a robust definition of sarcopenic obesity in the elderly is necessary for further clinical studies and interventions.